Transverse phase space diagnostics for ionization injection in laser plasma acceleration using permanent magnetic quadrupoles. (22nd February 2018) - Li, F; Nie, Z; Wu, Y P; Guo, B; Zhang, X H; Huang, S; Zhang, J; Cheng, Z; Ma, Y; Fang, Y; Zhang, C J; Wan, Y; et al.
Abstract: We report the transverse phase space diagnostics for electron beams generated through ionization injection in a laser-plasma accelerator. Single-shot measurements of both ultimate emittance and Twiss parameters are achieved by means of permanent magnetic quadrupole. Beams with emittance of μ m rad level are obtained in a typical ionization injection scheme, and the dependence on nitrogen concentration and charge density is studied experimentally and confirmed by simulations. A key feature of the transverse phase space, matched beams with Twiss parameter α T ≃ 0, is identified according to the measurement. Numerical simulations that are in qualitative agreement with the experimental results reveal that a sufficient phase mixing induced by an overlong injection length leads to the matched phase space distribution.